Identificación de Hongos Endófitos y su uso en la bioprotección de plántulas de Café para reducir el daño de Colletotrichum coffeanum en San Martin - Perú - Carbajal Alarcón, Frank Shamir (2016)
Coffee being grown in tropical climates, with a relatively high humidity is prone to many diseases of fungal type, and production is greatly affected by them, was affected in the last times. The use of endophytic fungi (Trichoderma sp, Asperllus sp, Verticilium sp) could be an alternative to solve these problems, with the objective of determining the influence of the best bioprotective isolates against Colletotrichum coffeanum. it was possible to identify eight endophyte fungi: Thichoderma sp, Aspergillus sp, Verticilium sp, Thielaviopsis sp, Scytalidium sp, Xylaria sp, Nigrospora sp and Pestalotiopsis sp in the dual test, the endophyte fungus Aspergilius sp, had the fastest growth and development linear of the colony, being that at 6 days (6th evaluation) reached its maximum development with 9 cm and at 4 days with a growth of 7.28 cm could control the growth and linear development of Colletotrichum sp colony that reached 1.66 cm. followed Trichoderma sp, reaching its maximum growth from 9 cm to 9th day (9th evaluation) and that with growth of 7,14 cm to the 5th day (5th evaluation) was able to control the growth and linear development of Colletotrichum sp colony that only reached 1, 82 cm. in the endophytic capacity, the plants inoculated with Trichoderma sp, Aspegillus sp and Verticilium sp had better effect obtaining greater number of leaves per plant, the size of the plants, Vigor of the leaves in addition did not present symptoms of disease, in contrast the plants inoculated with Thielaviopsis sp, Scytalidium sp, Xylaria sp, Nigrospora sp, Pestalotiopsis sp presented small leaves with chlorosis, with symptoms of stress and disease